ENTREPRENEURIAL COMPETENCE AND PERSONALITY AS DRIVERS OF ENTREPRENEURIAL COMMITMENT: A STUDY ON DISABLED MICRO-BUSINESS OWNERS - Ie, Mei; Maupa, Haris; Madris, Madris (International Journal of Application on Economics and Business, 2024)
Micro-enterprises have become one of the main drivers of economic growth, with business owners playing an important role in building the local economy. This presents both opportunities and challenges for people with disabilities who own micro-enterprises. One factor that is believed to have a major influence on entrepreneurial success is the entrepreneurial competence and personality of the business owner. Entrepreneurial competencies include the skills, knowledge and attitudes required to manage a business effectively. In addition, the personality of business owners is also thought to influence their commitment to their own business. A proactive, creative and risk-taking personality tends to be positively correlated with entrepreneurial commitment. The purpose of this study was to determine the effect of entrepreneurial competence and personality on the entrepreneurial commitment of micro business owners with disabilities. This study uses a quantitative descriptive approach using a questionnaire to obtain data with a sample of 133 respondents of micro business owners with disabilities in three cities in Central Java, Indonesia. This research uses primary data collected directly by the researcher. The data analysis technique uses PLS-SEM with SmartPLS 3.0. Based on hypothesis testing that has been carried out, it is found that entrepreneurial competence and personality have a positive effect on entrepreneurial commitment in micro business owners with disabilities located in three regions in Central Java.